FINANCIAL INCLUSION AND ITS TRENDS IN INDIAN ECONOMY - Mudasir Ahmad Ganai (RADJA PUBLIKA, 2023)
Abstract Finance has an essential part of an economic development of the society as well as in economic nations. Through financial inclusion can achieve equitable and inclusive growth of the country. Financial inclusion is used for delivery of appropriate financial services at an affordable cost, on the basis to vulnerable groups such as low income group and weaker section of people that lacks access to even the most basic banking services. This study is based on the focuses on approach adopted various Indian banks to achieving the goal of financial inclusion for inclusive growth in India. The reverent data has been collected from various articles, journals, report of RBI, report of NABARD and Annual Economic Survey. The above context is based on the financial inclusion and economic growth and finance in Indian context. In this research paper we learn about the effect of various financial inclusions on our nation’s economy